Quantitative assessment technique based on magnetic resonance image processing for determining the incidence of articular cartilage morbidity - Krishnaswamy, Abhirami. (2010)
BACKGROUND & MOTIVATION Knee osteoarthritis (OA) is caused by the progressive loss of articular cartilage and the parallel formation of osteocytes leading to tenacious affliction and functional restrictions in the affected joints. Pronouncement of the disease using MR imaging has become prevalent, where the damage, which is seen as brighter regions within the cartilage volume, may be visually diagnosticated by a trained radiologist. As a result, there is a need to better enable clinicians in performing an accurate analysis for their patients to determine if their cartilage has been damaged significantly, in particular, through quantitative metrology.